2012
DOI: 10.1021/jo300313v
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Seleninate Esters as Catalysts for the Oxidation of Sulfides to Sulfoxides, Epoxidation of Alkenes, and Conversion of Enamines to α-Hydroxyketones

Abstract: Cyclic seleninate esters serve as catalysts for the rapid oxidation of sulfides to sulfoxides, alkenes to epoxides, and enamines to α-hydroxyketones. Optimal conditions were found that minimize the overoxidation of the product sulfoxides to sulfones and the hydrolysis of epoxides to diols. In some examples such as styrene derivatives, oxidative cleavage was observed instead of epoxidation. The enamine oxidations proceed via the initial formation of dimeric 2,5-diamino-1,4-dioxane species, which were hydrolyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 108 publications
(61 reference statements)
3
35
0
Order By: Relevance
“…α-Methylstyrene oxide was converted to acetophenone under the reaction conditions, while α-methylstyrenediol did not react. Oxidations of morpholinyl enamines proceeds by the initial formation of diaminodioxanes, which are hydrolyzed in situ to give α-hydroxyketones such as 2-hydroxycyclohexanone [152].…”
Section: Organoselenium Compounds As Oxidizing Agents and Oxidatiomentioning
confidence: 99%
“…α-Methylstyrene oxide was converted to acetophenone under the reaction conditions, while α-methylstyrenediol did not react. Oxidations of morpholinyl enamines proceeds by the initial formation of diaminodioxanes, which are hydrolyzed in situ to give α-hydroxyketones such as 2-hydroxycyclohexanone [152].…”
Section: Organoselenium Compounds As Oxidizing Agents and Oxidatiomentioning
confidence: 99%
“…In order to gain further insight into this process, which has both biological relevance for these and other GPx mimetics, as well as potential synthetic utility, we embarked on a further study of the oxidation of dibenzyl disulfide with hydrogen peroxide in the presence of 1 , as well as its extension to a variety of other symmetrical and unsymmetrical disulfides. It is also worth noting that 1 is an effective catalyst for the oxidation of sulfides to sulfoxides, alkenes to epoxides and enamines to α-hydroxy ketones (Scheme 2) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the undesired deactivating effect of selenenyl sulfide formation noted previously, this indicates that the seleninate esters could also be capable of oxidizing other disulfide bonds, possibly including those of native proteins and peptides in vivo, resulting in potentially deleterious effects. Indeed, in related work, it was found that 10 a can catalyze the oxidation of sulfides to sulfoxides, alkenes to epoxides and enamines to α‐hydroxy ketones in a preparatively useful manner, while the similar oxidation of various disulfides to thiolsulfinates provides synthetic access to the latter class of compounds …”
Section: Cyclic Seleninate Estersmentioning
confidence: 99%